2020
DOI: 10.1108/bfj-10-2019-0817
|View full text |Cite
|
Sign up to set email alerts
|

Food-related lifestyle segmentation and beverage attribute' selection: toward understanding of sugar-reduced beverages choice

Abstract: PurposeAs the risks associated with sugar-sweetened beverages (SSBs) increase, various policies require sugar to be reduced in beverages. This paper segmented consumers according to food-related lifestyle (FRL), analyzed beverage selection attributes and preference for sugar-reduced beverages (SRBs) for each group and presented basic data for the strategies of SRBs for each consumer group.Design/methodology/approachIn total, 1,000 Korean consumer panels responded to the online survey. The questionnaire consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 40 publications
(59 reference statements)
5
27
0
Order By: Relevance
“…Moreover, this target group is comparable to that identified by Zakowska [40] among Polish food consumers, which attributed great importance to taste, safety, and price and did not care about product labels. Regarding sociodemographic variables, consumers grouped into this cluster, in line with Yeo et al [53], showed high education levels, although neither income nor age seemed to affect their attitudes towards fresh-cut fruits.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, this target group is comparable to that identified by Zakowska [40] among Polish food consumers, which attributed great importance to taste, safety, and price and did not care about product labels. Regarding sociodemographic variables, consumers grouped into this cluster, in line with Yeo et al [53], showed high education levels, although neither income nor age seemed to affect their attitudes towards fresh-cut fruits.…”
Section: Discussionsupporting
confidence: 77%
“…They loved to plan meals and paid attention to price, quality, and sensory traits. Similar to Yeo et al's study [53] with Korean consumers, in this cluster, price is an important criterion for choosing food as well as quality and sensory traits [42]. However, unlike these two previous studies, our group of consumers did not seem to consider product information and its freshness as decisive parameters for buying convenience products.…”
Section: Discussionsupporting
confidence: 56%
“…They are strapped to the finger by adhesive tape. The EDA sensor characteristics are described in Table 3, and the transfer function is given by Equation (3).…”
Section: Physiological Datamentioning
confidence: 99%
“…One of the big questions researchers are trying to answer nowadays is whether psychophysiological responses can provide new insights into the decision-making process of consumers. Specifically concerning edible products, there is a great interest in obtaining accurate and objective data about the sensory perception of food and beverages and, consequently, about consumption intention [ 2 , 3 , 4 ]. This field of study can be greatly reinforced through the development of new and more in-depth protocols of sensory analysis, capable of complementing self-reporting questionnaires with the use of psychophysiological traits.…”
Section: Introductionmentioning
confidence: 99%
“…
their targeted consumer segments. Lifestyle-based segmentation provides advantages of identifying consumer tendencies, values, attitudes, and behavior (Yeo et al, 2020).An interesting outline for this research problem is smartphone purchasing decisions. A smartphone is a lifestyle-laden product (Hamka et al, 2014) because it offers a set of integrated features such as text and voice devices, video, game, and internet for various functions including communication, social network, multimedia entertainment, mobile commerce, and more (Hamka et al, 2014).
…”
mentioning
confidence: 99%